2021
DOI: 10.2196/16824
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Management Guide (the DemPower App) for Couples Where One Partner Has Dementia: Nonrandomized Feasibility Study

Abstract: Background Promoting the health and well-being of couples where one partner has dementia is an overlooked area of care practice. Most postdiagnostic services currently lack a couple-centered approach and have a limited focus on the couple relationship. To help address this situation, we developed a tablet-based self-management guide (DemPower) focused on helping couples enhance their well-being and relationship quality. Objective The aim of this study i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Other studies were conducted in Australia ( n = 4), Canada ( n = 3), Hong Kong ( n = 1), and the US ( n = 7). Two articles included multi-national studies ( 56 , 57 ). Three research approaches were employed, including 12 quantitative, 11 qualitative, and 11 multi- or mixed-methods.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies were conducted in Australia ( n = 4), Canada ( n = 3), Hong Kong ( n = 1), and the US ( n = 7). Two articles included multi-national studies ( 56 , 57 ). Three research approaches were employed, including 12 quantitative, 11 qualitative, and 11 multi- or mixed-methods.…”
Section: Resultsmentioning
confidence: 99%
“…Bemelmans et al ( 60 ) reported on an intervention involving the social pet robot, PARO, to elicit social engagement and facilitate interactions between dyads. Two interventions employed mobile applications to promote self-management and social participation in community-dwelling caregiving dyads ( 56 , 69 ), while another intervention introduced a dementia assistance dog to support dyads at home ( 70 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Families, particularly couples affected by dementia, have to adjust to the transition from an interdependent relationship to a dyadic caregiving relationship of caregiver-care recipient [ 1 , 6 , 7 ]. This transition can negatively impact the relationship [ 8 ], influencing the well-being of both dyad members [ 9 , 10 , 11 , 12 ] and increasing the risk of unwanted institutionalisation [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%